The Role Of Advocates In Realizing Justice In Indonesia - Fauziah Lubis; Kurnia Fanny; Erwin, Erwin; Tasya Fadillah; Krisnadi Kusuma Suwandi; Franstogi Anugrahta Simbolon; Kamaluddin Simamora (SEAN Institute, 2025)
This study aims to analyze the role of advocates in realizing distributive justice and commutative justice, especially in the context of defending client rights in the legal system. The problem of this research focus on how advocates play a role in both types of justice, both in the fair distribution of resources ( distributive justice ) and in ensuring a balance of rights and Obsessions in relationships between individuals ( commutative justice ). This research is motivated by the strategic role of advocates in the justice system that can support the achievement of justice through defending the rights of individual and groups. Distributive justice is related to the fair distribution of resources, while commutative justice emphasizes the fulfillment of equal obligations in legal relationships between parties. This study uses a normative research method, namely by analyzing legal norms that regulate the role of advocates in realizing both types of justice, as well as various relevant legal literature. The roles of advocates shows that advocates have an important role in supporting distributive justice by helping marginalized or disadvantaged clients get their rights, and play a role in creating commutative justice by ensuring the exchange of rights and obligations between parties involved in the dispute. This study provides insight into the importance of the role of advocates in realizing more equitable and balanced justice in society.